A Critical Review of General Method and Game-based Method in Learning Time Dilation - Lok, Leh Leong; Abbas Saliimi, Lokman (2015)
This paper critically reviews general learning method and game-based learning method in Time Dilation of Special Relativity theory. People usually hard to grasp physics theory, particularly when they deal with equations or formulas such as Special Relativity. In physics, Special Relativity is the generally accepted physical theory involving the relationship between space and time. Special Relativity consists of the few effects such as Lorentz Transformation, Time Dilation, Space Wrapping which are exceedingly difficult for most people to understand it. This is because they never experience such phenomenon in everyday life. Thus, this paper discusses general learning methods like classroom learning, online learning with a game-based method through computer visualization in learning Time Dilation effect.